Implementasi Algoritme Grain V1 Untuk Enkripsi Gambar Pada Aplikasi Berbasis Web - Andhika Brahmana Putra; Ari Kusyanti; Mahendra Data (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
The challenge of dealing with illegal copying and distribution of multimedia documents is an important problem to be solved. Different techniques have been introduced such as encryption and digital watermarking to protect the data from unauthorized parties. In this study, data encryption is carried out in image format through web-based applications by using the Grain algorithm. Grain algorithm has an advantage of that it reduces the value of complexity and increases the speed of computing. Tests carried out are test vector validation testing, encryption and decryption validation testing, encrytime performance testing and security testing. The result of test vector, encryption and decryption validation test are valid. For encryption and decryption execution time of each image file extension resulted the longest execution time is on JPG extension files while the shortest execution time is on BMP.While for security testing obtained sniffing results using Wireshark which shows that the encrypted data is unknown to an authorized party. The conclusion of the above test is that the Grain algorithm can be performed by applying an image encryption mechanism that can protect data confidentiality.